Address forms in Chinese audit opinions - Ziye Zhao (China Journal of Accounting Research, 2014)
Although forms of address are widely used in textual and other types of disclosure, empirical evidence of their effects is rare. China provides a unique setting in which to test the economic consequences of the forms of address used in audit reports. From 2003 to 2011, about 60% of auditors surveyed addressed their clients by their real names in audit opinions, while the others used honorifics. Based on a sample of Chinese audit opinions, I report the following findings. First, the announcement of an audit opinion that uses the client's real name elicits a greater market response than the announcement of an opinion featuring an honorific form of address. Second, the effects of real-name forms of address are stronger in firms with weak board governance. Third, the association between audit fees and audit risk factors, such as loss-making, is stronger in firms that are addressed by their real names in audit reports. I conclude from these findings that the forms of address used in audit opinions may reveal private information on audit quality. The results of this study are consistent with the power-solidarity effect described by sociolinguists.
Keywords: G11; L20; M42; 650; Address forms; Audit independence; Power-solidarity effect; Politeness principle